Upaya Peningkatan Pelayanan Kesehatan Primer dalam Pengendalian Hipertensi dengan Terapi Akupresur pada Masyarakat - Cahyaningrum, Ika; Rere, Theresia Beto Suku; Khairunnisa, Fitri; Kurmiyati, Fauziyah; Erwanto, Erwanto (Jurnal Abdimas Kesehatan (JAK), 2026)
The incidence of hypertension in Wagir Subdistrict, Malang Regency, remains quite high. At the Bunder Village Health Center in Sidorahayu Village, 15 out of 32 active participants suffer from hypertension. Efforts to improve primary health care in the management of hypertension through acupressure therapy. This community service activity involves providing complementary acupressure therapy to Posyandu participants and educating health cadres on acupressure points as part of primary health care. This activity was carried out in February 2025 at the Bunder Village Posyandu, Sidorahayu Village, Wagir District. From this activity, there was a decrease in the average blood pressure value in hypertensive patients after receiving acupuncture therapy and an increase in the knowledge and skills of health cadres regarding acupuncture points to overcome hypertension symptoms. It is hoped that acupressure therapy can be applied by Posyandu health cadres as a promotive effort and complementary therapy to overcome the symptoms of hypertensive patients.